Otopná soustava knihovny - Dlabajová, Pavlína (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Závěrečná práce řeší vytápění univerzitní knihovny Přírodovědecké fakulty Masarykovy univerzity, situované na ulici Kotlářská 267/2, 611 37 Brno. Projekt se zabývá výpočtem tepelného výkonu, návrhem zdroje tepla, přípravy teplé užitkové vody, otopných ploch a návrhem přípravy teplé vody pro vzduchotechniku. Dimenzováním a hydraulickým posouzením potrubí, návrhem čerpadel a zabezpečovacího zařízení.

This study presents the structure of the heating system in the library of Masaryk University of Science with the address Kotlarska 267/2, 611 37 Brno. In particular, this study will examine the calculations of the heating output, proposals for sources of the heating output, preparation of the hot water, heating surfaces and the proposal for the hot water for the hydraulic piping. Additionally, the author will conduct an evaluation of the dimensions as well as a hydraulic assessment of the pipeline, the design of the pumps, and lastly the safefy equipment.
Heating System of Libraries
Keywords: Vytápění; příprava teplé vody; podlahové topení; Heating; hot water production; floor heating